Methylphenidate, Academic Performance, and Behavior - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The effects of 0.3 mg/kg and 1.0 mg/kg of methylphenidate on the overt behavior and academic functioning of 12 children with ADDH are reported from the Department of Psychiatry Research, Hospital For Sick Children, Toronto, Ontario, Canada.